Association of the HLA-DQA1 and HLA-DQB1 Alleles in Type 2 Diabetes Mellitus and Diabetic Nephropathy in the Han Ethnicity of China. (26th February 2013) - Ma, Ze-Jun; Sun, Pei; Guo, Gang; Zhang, Rui; Chen, Li-Ming
Abstract : HLA gene system is one of the most polymorphic regions of the human genome. The association of HLA class II genes in T1DM pathogenesis has been reported for several ethnicities. Associations of HLA class II genes with T2DM have revealed inconsistent results. Moreover, correlations between DN and HLA alleles remain unclear. We carried out DNA typing chip by specific medium resolution typing probes in 310 T2DM subjects (including 210 patients with DN and 100 patients without DN) in addition to 100 healthy controls. Differences were found between patients with T2DM and the control group in the frequencies of the HLA-DQA1*0301 (15.5% versus 8.0%, P < 0.01 ) and the HLA-DQA1*0501 alleles (16.6% versus 8.5%, P < 0.01 ). Differences were found between patients with DN and without DN in the frequencies of the HLA-DQA1*0302 (6.9% versus 13.5%, P < 0.01 ) and HLA-DQB1*0501 alleles (5.8% versus 14.5%, P < 0.01 ). Diabetes duration and systolic blood pressure were independent risk factors associated with DN (OR = 2.277 and 1.366, resp., P < 0 .05 ), whereas the HLA-DQB1*0501 llele had a protective effect on DN (OR = 0.53, P < 0 .05 ). These data suggest the HLA-DQA1*0301 and HLA-DQA1*0501 alleles are markers of susceptibility for T2DM, and the HLA-DQB1*0501 allele is associated with a protective effect on DN in Han ethnicity of China.